Nutritional and food security status of orphans and vulnerable children: report of a research project supported by UNICEF, IFPRI, and WFP - Rivers, Jonathan; Silvestre, Eva; Mason, John B. (Tulane University, 2004)
The HIV epidemic has created over 10 million orphans in sub-Saharan Africa and countless other children are affected by the disease, whether by living with a parent who is chronically ill or living in a household that is hosting orphans. Mortality rates for adults are rising rapidly, for women now faster than men. While efforts are aimed at preventing future orphans, many more children will lose their parents before the epidemic is under control. One of the major challenges facing governments, international organizations and NGOs in their response is the lack of data on the situation of orphans and the quality and effectiveness of their interventions. Continuous assessments of national strategies aimed at improving the welfare of orphans are needed in order to assess the effectiveness of these interventions. A key area is the food and nutrition situation of orphans and other children made vulnerable by HIV/AIDS. Inconsistent findings make it difficult to assess if orphans and other vulnerable children have specific nutritional needs separate from other children. This report looks to answer this question by establishing the present nutritional status of orphans in sub-Saharan Africa by examining a large number of countries in the region. Specifically, the report answers: a) To what degree is child anthropometry and household food security affected by orphan-hood and chronic sickness?, b) Is underweight the most appropriate indicator to measure the nutritional status of orphans?, c) Which types of households are most affected by food insecurity and which indicators show promise for future monitoring?, and d) How does the concept of vulnerability relate to food security? -- from Author's Introduction."